2015
DOI: 10.1371/journal.pone.0126015
|View full text |Cite
|
Sign up to set email alerts
|

A Role of Myocardin Related Transcription Factor-A (MRTF-A) in Scleroderma Related Fibrosis

Abstract: In scleroderma (systemic sclerosis, SSc), persistent activation of myofibroblast leads to severe skin and organ fibrosis resistant to therapy. Increased mechanical stiffness in the involved fibrotic tissues is a hallmark clinical feature and a cause of disabling symptoms. Myocardin Related Transcription Factor-A (MRTF-A) is a transcriptional co-activator that is sequestered in the cytoplasm and translocates to the nucleus under mechanical stress or growth factor stimulation. Our objective was to determine if M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 86 publications
(111 reference statements)
2
55
0
Order By: Relevance
“…We infer from our data that Hic-5-dependent sustained development of stress fibers in pathogenic myofibroblasts supports persistent MRTF-A localization, thereby perpetuating the myofibroblast phenotype. Consistent with this notion is the observation that small molecules that promote MRTF-A function result in quicker wound closure (Velasquez et al, 2013), whereas MRTF-A inhibitors can reduce fibrotic markers in scleroderma mouse models Shiwen et al, 2015).…”
Section: Discussionmentioning
confidence: 88%
“…We infer from our data that Hic-5-dependent sustained development of stress fibers in pathogenic myofibroblasts supports persistent MRTF-A localization, thereby perpetuating the myofibroblast phenotype. Consistent with this notion is the observation that small molecules that promote MRTF-A function result in quicker wound closure (Velasquez et al, 2013), whereas MRTF-A inhibitors can reduce fibrotic markers in scleroderma mouse models Shiwen et al, 2015).…”
Section: Discussionmentioning
confidence: 88%
“…MRTF-A interactions with YAP have generated substantial interest in the nuclear localization patterns of MRTF-A (58-60), but to date nearly all investigations that test stiffness variations have analyzed only two distinct values (61,62). Leveraging our gradient system, we analyzed expression patterns of MRTF-A and MRTF-B in hASCs plated for 24 h on 2.9-kPa/mm hydrogels and found that although MRTF-B localization was independent of stiffness ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study indicated that type I collagen synthesis depended on MRTF-A activation. 58 Therefore, MRTF-A was activated and translocated to the nucleus under 4% strain stimulation, and then induced collagen synthesis. However, the results of in vitro study were not consistent with the findings in vivo.…”
Section: Discussionmentioning
confidence: 97%